Kajian Tri Hita Karana Dalam Perayaan Tumpek Wariga - Ni Nengah Nani Martini (Kamaya: Jurnal Ilmu Agama, 2019)
Bali is famous for its culture because of the uniqueness and distinctiveness that grows from the spirit of Hinduism. Every religious activity contains religious and spiritual elements, and this belief is still brought to the present by Balinese Hindus. Hindus have a way to show their gratitude to nature who have given life prosperity by means of a ceremony called Tumpek Wariga. For some Balinese Hindus the meaning of what is behind the Tumpek Wariga celebration is not the main thing. Society dissolves in celebration without knowing its meaning and essence. On the other hand it appears that now the Tumpek Wariga tradition in its meaning appears to be still lacking, this can be seen from the year to year period many green lines are converted into housing, floods and landslides occur in some areas during the rainy season. In collecting data, this study uses observation, interview and literature study methods. The technique used to collect data in this research is descriptive qualitative approach. Implementation Tumpek Wariga in Sulahan Village flows from the concept of Tri Hita Karana. Tumpek Wariga's Impilaksi towards the people in the village of Sulahan is expected to increase the public's understanding of the importance of protecting the environment both horizontally and in a way that is for the sake of human survival.